Highly oriented and fully dense CGO films prepared by spray-pyrolysis and different precursor salts. - Dos-Santos-Gómez, Lucía; Zamudio-García, Javier; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (Elsevier, 2020)
CeO2–based thin films are prepared by spray-pyrolysis deposition from different aqueous precursor solutions containing nitrate, chloride or acetate salts. The morphology and orientation growth strongly depends on the precursor type. Acetate solutions lead to dense films with improved microstructural features, i.e. uniform film thickness and a low roughness of 1.5 nm. Films with different Gd-content (Ce1-xGdxO2-x/2, 0≤x≤0.2, CGO) are prepared from acetate salts. These films show a (200) preferred orientation growth, regardless of the substrate type, i.e. fused quartz and polycrystalline ceramics. The in-plane conductivity of the films on quartz is lower than that of the bulk material, possibly due to the different thermal mismatch between the substrate and the film. These CGO films are also evaluated as protective layers to prevent the reaction between the Zr0.84Y0.16O1.92 (YSZ) electrolyte and the La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) cathode. The electrode efficiency of LCSF improves greatly after the introduction of a 150 nm thin CGO interlayer
Keywords: Pilas de combustible; Electroquímica; Solid oxide fuel cells; Spray-pyrolysis